Amount and spatial distribution of habitats influence occupancy and dispersal of frogs at multiple scales in agricultural landscape. (21st November 2020) - Faggioni, Gabriel P.; Souza, Franco L.; Paranhos Filho, AntÔnio C.; Gamarra, Roberto M.; Prado, Cynthia P. A.
Abstract: Agriculture changes the aquatic and terrestrial habitats used by animals, affecting their responses to matrix permeability. Here, we evaluated the impacts that resulted from the replacement of native vegetation with pastures on habitat occupancy, colonisation and local extinction of two Neotropical frogs with contrasting ecological strategies, Leptodactylus bufonius and L. chaquensis . We conducted fieldwork during two reproductive seasons in 50 temporary ponds in the Brazilian Chaco. We used site occupancy models in a multi‐scale approach to identify landscape changes affecting population parameters and to determine the scale of interaction between species and the landscape. At local (10 m) and scales ≤400 m, increased pasture proportion limited the availability of bare soil required by males of L. bufonius to build mud chambers for reproduction and decreased proportion of shrublands affecting L .  chaquensis occupancy. At larger spatial scales (>400 m), landscape modification limited dispersal of the smaller species L. bufonius . We found that the amount of habitat available is important in maintaining population parameters such as occupancy. However, our results highlight that the spatial distribution of habitats may also play an important role in the persistence and mobility of frogs in agricultural landscapes and that it is possible to identify a scale of effect in such anthropic landscapes. We recommend the consideration of reproductive and dispersal requirements of amphibian species, along with body size, as predictors of the spatial scale for management of populations in farmlands. Resumo: A agricultura altera os habitats utilizados pelos animais, afetando suas respostas em relação à permeabilidade da matriz. Nesse trabalho, nós investigamos os impactos resultantes da substituição de vegetação nativa por pastos na ocupação de habitat, colonização e extinção local de duas rãs Neotropicais que apresentam distintas estratégias ecológicas, Leptodactylus bufonius e L. chaquensis . Os trabalhos de campo foram realizados durante duas estações reprodutivas em 50 poças temporárias no Chaco Brasileiro. Utilizamos modelos de ocupação de hábitat, por meio de uma abordagem de múltiplas escalas, para identificar mudanças na paisagem que afetem parâmetros populacionais e para determinar a escala de interação entre as espécies e a paisagem. Na escala local (10 m) e em escalas ≤400 m, o aumento na proporção de pasto limitou a disponibilidade de solo exposto necessário para que machos de L. bufonius construam suas câmaras para a reprodução e diminuiu a proporção de áreas arbustivas, afetando a ocupação por L. chaquensis . Em escalas espaciais maiores (>400 m), as modificações na paisagem limitaram a dispersão da menor espécie, L. bufonius . Verificamos que a quantidade de hábitat disponível é importante para definir a proporção de ocupação. Entretanto, nossos resultados destacam que a distribuição espacial dos hábitats também pode ser importante para a persistência e mobilidade de rãs em paisagens agrícolas e que é possível a identificação da escala de efeito em tais paisagens antropizadas. Recomendamos a inclusão de atributos reprodutivos e de dispersão das espécies, juntamente com tamanho do corpo, como preditores da escala espacial para o manejo de populações em paisagens agrícolas. Abstract in Portuguese is available with online material. Palavras‐chave: Amphibia, Chaco, ecologia de paisagem, ecologia de populações, escala de efeito.